Sputtering of tungsten exposed to high-flux and high-fluence hydrogen ion beam - Bizyukov, I.A. (Вопросы атомной науки и техники, 2013)
Tungsten samples were irradiated by hydrogen ion beam with high heat (0.1…1.05 MW·m⁻²) and particle [(0.13…1.3)×10²² m⁻²s⁻1] flux generated by FALCON ion source. The sputtering yield has remained nearly constant in the given flux range. Scanning electron microscope (SEM) studies of the irradiated surface have indicated that the only influence of the ion beam in the fluence range up to 2.6×10²⁶ m⁻² is the increase of roughness.